Does culture matter? driving safety compliance from leadership through safety culture - Amru, Muhammad Fahizza; Etikariena, Arum; Hidayat, Noor Shabrina (Jurnal Psikologi Tabularasa, 2025)
Workplace safety is vital for employee well-being and organizational success, especially in high-risk sectors like Indonesia’s energy industry. In Indonesia, the number of workplace accidents increased from 370,747 cases in 2023 to 462,241 in 2024. The energy sector is one of the largest contributors to workplace accidents in Indonesia. Ensuring safety compliance is key, and safety leadership is recognized as a major enabler, though its relationship to compliance is not fully understood. This study examines how safety culture mediates the effect of safety leadership on compliance in high-risk organizations. Using a quantitative cross-sectional design, data were collected from 202 employees of a multinational mining company and analyzed with Hayes’ PROCESS Model 4. Instruments were adapted to Indonesian and tested for reliability. Findings show that safety culture partially mediates the relationship between safety leadership and safety compliance. The results highlight the need for organizations to empower leaders to actively promote safety leadership in order to boost compliance with occupational safety standards.